Mild Traumatic Brain Injury in a High School Football Player With Familial Hemiplegic Migraine: A Case Report. Issue 4 (14th September 2017) - Chand, Manisha R.; Kanwar, Sumit; Peck, Evan
Abstract: Mild traumatic brain injury is a major concern in young athletes, with an estimated 1.6‐3.8 million reported concussions in the United States annually. Familial hemiplegic migraine is a rare autosomal‐dominant condition characterized by sporadic episodes of transient unilateral motor weakness that may begin at any age. We present a case of a 17‐year‐old boy with a history of familial hemiplegic migraine who suffered prolonged symptoms after a mild traumatic brain injury during sports participation. Level of Evidence: V